Engaging people with lived experience on advisory councils of a national not-for-profit: an integrated knowledge translation case study of Heart & Stroke Mission Critical Area Councils - Krystina B. Lewis; Nedra Peter; Heart & Stroke Foundation of Canada; Ian D. Graham; Anita Kothari (BMC, 2022)
Abstract Background In 2018, the Heart and Stroke Foundation of Canada transformed its approach to organizational strategic planning and priority-setting. The goal was to generate impact from bench to bedside to community, to improve the health of Canadians. It engaged researchers, clinician scientists, health systems leaders, and community members including people with lived experience (PWLE) on six Mission Critical Area (MCA) councils, each of which was co-chaired by a researcher or clinician scientist and a person with lived experience. Together, council members were tasked with providing advice to Heart & Stroke about the most relevant and impactful priorities of our time. The aim of this research was to explore the value of the MCA councils to Heart & Stroke, and to council members themselves. The research questions focused on understanding the process of managing and participating on the councils, the challenges and outcomes. Methods  Using an integrated knowledge translation approach, we conducted a case study with developmental evaluation over a 2-year time period (2018-2020). We collected qualitative data from various sources (Heart & Stroke team responsible for managing the councils, council co-chairs, council members, and key informants). We collected documents and analysed them for contextual background. Results  Participants noted that the MCA councils continuously evolved over the 2 years in various ways: from an uncertain direction to a concrete one, better integrating the voice of PWLE, and increased cohesiveness within and across MCA councils. This evolution was achieved in parallel with successes and challenges at three levels: the MCA councils and its members, Heart & Stroke, and Canadians. The MCA councils were disbanded in 2020, yet learnings, developments, initiatives and established partnerships remain as their legacy. Conclusions  Heart & Stroke's intended objectives for the MCA councils, to promote engagement and dialogue among community members including PWLE, clinician scientists, and researchers, and to provide advice into Heart & Stroke's strategic renewal process, were achieved. This collaborative structure and process for PWLE engagement within a community of multidisciplinary clinician scientists and researchers is possible yet requires flexibility, commitment to stakeholder relationship management, and considerable resources. These findings may be helpful for other not-for-profit and funding organizations interested in engaging the public and other stakeholders into their organizational activities.